Comparative Morphometric Analysis of Iraqi Sheep (Ovis Aries) and Goats (Capra Hircus) Papillary Muscles, Tendinous Chords, and Os Cardis: Cardiac Anatomy - AL-Mahmodi, Aqeel Mohsin Mahdi (American Journal of Biomedicine and Pharmacy, 2025)
Functionally relevant components of the atrioventricular valve complex include papillary muscles and chordae tendineae, which facilitate competent valve closure and unidirectional blood flow. Although comparative information on morphometric and anatomical differences in these structures is key, it is limited in domestic ruminants. For comparison of anatomical position, shape, number, and morphometric sizes of papillary muscles and chordae tendineae in sheep and goats' hearts, and evaluation of their functional implications. Methods: The hearts of eight healthy adult goats and eight healthy adult sheep were included in this research. Individual details of the chordae tendineae and papillary muscles (origin, insertion, length, number, arrangement etc.) were detected and measured through careful dissections. Statistical analysis and interpretation of the morphometric observations were made in the light of the established physiological functions of these structures. Similar observations were made in goats and sheep, with goat hearts having smaller, less prominent papillary muscles and thinner, less organized chordae tendineae when compared with sheep. Papillary muscles were found on the ventricles of both species, with species based differences in number and form. Interspecies differences in the length and diameter of the chordae tendineae with varying patterns of branching and points of insertion (p < 0.05). These morphologic differences suggest adaptations associated with optimal hemodynamics and species-derived cardiac requirements. These structural differences appear to be consistent with functional specialization between the sheep and goats. These observations extend the current knowledge of ruminant cardiac anatomy and may be of value in ruminant veterinary cardiac diagnostics and interventions in the future.